Cooked Food Supply Chain with ERP Model - P, Harshini; C., Sangeetha (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In order to assess how technology, in particular Industry 4.0 tools, has solved issues in the food supply chain, with an emphasis on quality, safety, and sustainability, this research systematically reviews literature from 2010 to 2021. The COVID-19 interruptions highlight the necessity of ongoing change in the direction of a food supply chain that is more robust and sustainable. This conceptual research examines the rapidly developing Indian online food start-up market, highlighting cutting-edge tactics and technology used by significant firms such as Zomato and Swiggy. The 350 billion Indian internet food sector is examined, with a focus on the factors that have contributed to these platforms’ success. Businesses must take a global viewpoint into account when analysing their competitive strategies in the current global business climate. This essay examines the fundamentals, obstacles, and tactics of supply chain management . concentrating on companies who operate in international markets, with a focus on the ramifications for the Indian agri-food industry.